2021
DOI: 10.3390/jcm10051032
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Comparisons among Inotropic Agents on Mortality and Risk of Renal Dysfunction in Patients Who Underwent Cardiac Surgery: A Network Meta-Analysis of Randomized Controlled Trials

Abstract: Several kinds of inotropes have been used in critically ill patients to improve hemodynamics and renal dysfunction after cardiac surgery; however, the treatment strategies for reducing mortality and increasing renal protection in patients who underwent cardiac surgery remain controversial. Therefore, we performed a comprehensive network meta-analysis to overcome the lack of head-to-head comparisons. A systematic database was searched up to 31 December 2020, for randomized controlled trials that compared differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 68 publications
(23 reference statements)
1
15
0
1
Order By: Relevance
“…As a result of increased hemolysis due to the use of blood products, renal injury may occur due to hemolysis-derived products [Freeland 2015]. Inotropic support may cause renal damage due to vasoconstrictive effects [Chen 2021]. In our study, we identified increased blood product and inotropic support use as independent predictors in predicting the development of AKI.…”
Section: E654mentioning
confidence: 61%
“…As a result of increased hemolysis due to the use of blood products, renal injury may occur due to hemolysis-derived products [Freeland 2015]. Inotropic support may cause renal damage due to vasoconstrictive effects [Chen 2021]. In our study, we identified increased blood product and inotropic support use as independent predictors in predicting the development of AKI.…”
Section: E654mentioning
confidence: 61%
“…Based on the literature research, the following five of the nine significant variables were included into multivariate binary logistic regression (see Table 3 ): ECMO [ 9 , 10 , 11 ], all cause infection after surgery [ 12 , 13 ], levosimendan [ 14 , 15 , 16 ], duration of NE therapy [ 17 , 18 , 19 ] and increase in Tacrolimus plasma levels [ 18 , 20 , 21 ]. Evidence for the choice to include these five variables can be found as references next to each variable.…”
Section: Resultsmentioning
confidence: 99%
“…A further contribution to understanding the renal effects of levosimendan may be found in the work of Chen et al, who conducted a network meta-analysis of 29 published trials to provide direct comparisons of levosimendan versus placebo or inotropes in patients undergoing cardiac surgery. [ 63 ] They concluded that, compared with placebo, the use of levosimendan significantly decreases the risks of mortality (OR 0.74; 95% CI [0.56–0.97]) and acute renal injury (OR 0.61; 95% CI [0.45–0.82]), especially in patients with low systolic function. [ 63 ] Comparisons with milrinone, dopamine, dobutamine and fenoldopam identified levosimendan as the best treatment based on p-values.…”
Section: Expert Assessmentmentioning
confidence: 99%